2014
DOI: 10.1590/s1517-83822014000400048
|View full text |Cite
|
Sign up to set email alerts
|

Experimental infection of BHK21 and Vero cell lines with different Mycoplasma spp.

Abstract: Mycoplasma spp, belongs to the class Mollicutes and is capable to produce alterations in cellular cultures causing damages to the biotechnological industry. Bioproducts generally require two essential inputs, bovine serum and cells. The study herein aims to evaluate the mycoplasma concentrations that affect the growing of BHK21 and Vero cells. The species used were: Mycoplasma orale, M. salivarium, M. arginini and M. hyorhinis, cultivated in a SP4 media. Two contamination tests were performed with BHK21 and Ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
(10 reference statements)
0
1
0
1
Order By: Relevance
“…Generally, there is a decline in the nutritional quality perceived of the culture medium (depletion of sugars, amino acids and fatty acids and cholesterols) (Masukagami et al, 2017). Some mycoplasmas may cause severe cytopathic effect, which can be characterized by slow growth, atrophied, rounded or degenerated cells (Netto et al, 2015;Hegde et al, 2016). Genomic analyzes have revealed that they possess a strict biosynthetic capacity which benefits them in the competition for macromolecules available in the culture medium (Poveda, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Generally, there is a decline in the nutritional quality perceived of the culture medium (depletion of sugars, amino acids and fatty acids and cholesterols) (Masukagami et al, 2017). Some mycoplasmas may cause severe cytopathic effect, which can be characterized by slow growth, atrophied, rounded or degenerated cells (Netto et al, 2015;Hegde et al, 2016). Genomic analyzes have revealed that they possess a strict biosynthetic capacity which benefits them in the competition for macromolecules available in the culture medium (Poveda, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Una vez que se alcanzó una cinética de crecimiento adecuada, el cultivo se transfirió a un frasco de cultivo mayor (T-75).Control de contaminación del cultivo celular por Mycoplasma spUna de las contaminaciones más abundantes en los cultivos celulares es la que se produce por algunas especies de Mycoplasma. Éstas pueden encontrarse en la piel humana, y contaminar los cultivos celulares por manipulaciones poco asépticas o por la utilización de sueros o tripsinas previamente contaminados, provocando alteraciones metabólicas, de la tasa de proliferación y de la capacidad antigénica(229).La contaminación por Mycoplasma puede pasar inadvertida en una observación rutinaria del cultivo, ya que se trata de células procariotas que forman pequeñas colonias no distinguibles fácilmente(230).…”
unclassified